Pirate Treasure: stolen riches - O'Donnell, Liam. (Mankato, MN Capstone Press, 2007)
Describes the things that pirates considered treasure, how they got their treasure, and what they did with it.
Elementary
Keywords: Pirates; Capture at sea; Treasure troves